Sistematización de experiencias de periodismo en tiempos de covid-19 en Machala - Espinoza Balcázar, Jéssica Paola; Gutierrez Valdiviezo, Ginger Yamileth (Machala, 2022)
This research work will be shown through the results of interviews with journalists active in the pandemic and the topic of how important journalistic work is in the city of Machala in times of COVID-19. The objective is through the systematization of experiences of professional journalists active during the pandemic, who were decorated by the ECU-911, through experiences lived by social communicators, challenges and challenges that they have had to overcome in order to continue providing information to the society. The collection of information will be based on the analysis of the importance of the journalistic exercise during this time that has changed the lives of all Ecuadorians and the way they have had to adapt to the new normality. The analysis and interpretation will be carried out by the same of all the information collected through the interviews that consist of 8 questions, in addition to the bibliographic review of scientific articles referring to the journalistic exercise of active journalists during the pandemic and everything they had to face to bring first-hand information to the Machaleña society. The systematization of the experiences of the journalists made to 25 local and national journalists contributed so that the investigation is based on our results obtained through the qualitative method with the use of techniques such as the interview, bibliographic review and focus group. The main findings that were evidenced were that the adaptation to the context was a considerable challenge and challenge that journalists knew how to overcome with responsibility and ethics to carry out their day-to-day work to get information to homes through the different mass media being the digital media the main tools for information to arrive directly, obviously reminding citizens to contrast information and consume from official sources. In addition to the bibliographic review carried out in the 25 scientific articles, it is important to highlight the importance of the investigations with reference to our topic, which was of great help because it makes it easier for us to find valuable information about the systematization of experiences of communicators and journalists at the beginning, during and until news about the Covid-19 pandemic.
El presente trabajo de investigación se mostrará a través de resultados de entrevistas a periodistas activos en pandemia y el tema acerca de qué importante es la labor periodística en la ciudad de Machala en tiempos de COVID-19. El objetivo es a través de sistematización de experiencias de periodistas profesionales activos durante la pandemia, que fueron condecorados por el ECU-911, mediante experiencias vividas por parte de los comunicadores sociales, retos y desafíos que han tenido que vencer para poder seguir brindando información a la sociedad. La recolección de información se hará en función del análisis sobre la importancia del ejercicio periodístico durante este tiempo que ha cambiado la vida de todos los ecuatorianos y la forma que han tenido que adaptarse a la nueva normalidad. Se realizará el análisis e interpretación de las mismas de toda la información recolectada mediante las entrevistas que constan de 8 preguntas, además de la revisión bibliográfica de artículos científicos referente al ejercicio periodístico de los periodistas activos durante la pandemia y todo lo que tuvieron que enfrentarse para llevar información de primera mano a la sociedad machaleña. La sistematización de las experiencias de los periodistas realizadas a 25 periodistas locales y nacionales contribuyó para que la investigación se fundamente nuestros resultados obtenidos a través del método cualitativo con la utilización de técnica como la entrevista, revisión bibliográfica y focus group. Los principales hallazgos que se evidenciaron fueron que la adaptación al contexto fue un reto y desafío considerable que con responsabilidad y ética periodista supieron superar para realizar su labor dia a dia para hacer llegar la información a los hogares a través de los diferentes medios masivos siendo los medios digitales las principales herramientas para que la información llegue de forma directa, obviamente recordando a la ciudadanía que contraste la información y que consuma de fuentes oficiales. Además de la revisión bibliográfica realizada en los 25 artículos científicos es importante resaltar la importancia de las investigaciones con referencia a nuestro tema fue de gran ayuda porque nos facilita encontrar información valiosa acerca de las sistematización de experiencias de comunicadores y periodistas al inicio, durante y hasta la actualidad sobre la pandemia de COVID-19.
Keywords: LABOR PERIODISTICA; TRATAMIENTO DE INFORMACION; COBERTURA INFORMATIVA; EXPERIENCIA COMUNICATIVA; PANDEMIA; SOCIEDAD DE INFORMACION; PERIODISMO INDEPENDIENTE